A versenyképesség kulturális és humán aspektusai - Fazekas, Nikolett; Fábián, Attila (Közép-Európai Közlemények, 2015)
My research interprets the success of the enterprise’s thesis as an example of an international multi-site company. It identifies the success of the corporate site selection’s criteria, based on the traditional theories, but using the new practical methods of the international and regional abundance of success. I recommend a coordinated method–setting up an own model–, which allows detailed information to company management and their use can precisely define the methodology of strate-gically and cost-effective appropriate site selection. I analyzed countries and regions by institutional and social changes, in order to explain the differences of success. My dissertation highlights the fact, that for the decision-making, which competitiveness indicators would be desirable to be used. Furthermore it shows how the quality of social environment and social capital influences the decision-making. Of course I do not dispute, that there can be direct economic reasons of the success of the location choices, but in the model we complemented (refined) this aspect with a detailed correlation analysis and assessment of the variables representing the regional competitiveness. My inference, which can be deducted from the regions’ analysis is, that the results of the current methods, which are used for the selection of premises, do not imply enough information for the companies’management for optimal decision-making.